Calculation of Copper Production Failure Risk Level Based on Aggregate Loss Cost - Wijaya, Alvian Octa; Thufeil Rafi, Muhammad (International Journal of Global Operations Research, 2024)
In its implementation, the copper manufacturing industry often faces various risks, one of which is the risk of production failure. This research aims to calculate the level of risk of factory failure in producing copper based on aggregate loss costs. Quantitative methods were used in this research. It calculates the failure frequency, which follows a Poisson distribution, the loss distribution, which follows an exponential distribution function, and the total loss amount.